"An ignorant on the subject" : How to speak of an eminent musicologist telling the story of someone who knew stories (Mayéutica Revista Científica de Humanidades y Artes, 2023)
The figure of Juan Francisco Sans represents for Latin American musicology one of the most important references of recent years. His vast work, his great capacity for dedication and commitment to knowledge, as well as to musical practice, constitute today an inescapable example of a professional of integrity in every sense of the word. In my short friendship I had the opportunity to tell him about my concerns and aspirations in research, and thus receive his guidance with unparalleled generosity. These words serve to honour the memory of one of the greatest musicologists in the world. All this from a story that evidences his noblest facet: research, disseminate and teach.
Keywords: Juan Francisco Sans; musicology; artistic research; music education; Venezuela